Covid lockdowns in the UK: Estimating their effects on transmission. Issue 2 (29th March 2022) - Prestige, Emily; Stander, Julian; Wei, Yinghui
Abstract : UK citizens have lived through three lockdowns over the course of the Covid‐19 pandemic. What effect have these restrictions had on the transmission of the virus? Emily Prestige, Julian Stander and Yinghui Wei investigate Abstract : UK citizens have lived through three lockdowns over the course of the Covid‐19 pandemic. What effect have these restrictions had on the transmission of the virus? Emily Prestige, Julian Stander and Yinghui Wei investigate